Managing acute kidney injury in a child with improvised peritoneal dialysis in Kano, Nigeria - Obiagwu, Patience; Gwarzo, Garba; Akhiwu, Helen; Wada, Aminu (Nigerian Journal of Basic and Clinical Sciences, 2026)
Acute kidney injury (AKI) is a relatively common condition in children. Management is daunting in resource-limited settings. This is a case report of a 5½-year-old girl who developed AKI secondary to hemolytic-uremic syndrome and managed with improvised peritoneal dialysis. A 5½-year-old girl presented to the emergency unit with features of acute renal failure following a febrile illness. A diagnosis of hemolytic-uremic syndrome was made. Peritoneal dialysis was commenced using improvised dialysis fluid, peritoneal catheter and drain set. She had an average of five cycles daily for 16 days with significant improvement in her clinical and laboratory parameters. After 4 weeks on admission, she was discharged home in a clinically stable state. The management of AKI, though challenging, can be achieved with improvised peritoneal dialysis in resource-limited settings.